2019
DOI: 10.1177/1177180119835228
|View full text |Cite
|
Sign up to set email alerts
|

“We are not privileged enough to have that foundation of language”: Pasifika young adults share their deep concerns about the decline of their ancestral/heritage languages in Aotearoa New Zealand

Abstract: Focus group interviews conducted with Aotearoa New Zealand–born Pasifika young adults aged 18–25 years highlighted their intense apprehension about the diminishing abilities of New Zealand–born Pasifika people to speak their ancestral/heritage Pasifika languages in Aotearoa. Some Pasifika languages are also declining at their homeland wellsprings. There has been no comprehensive strategic national language policy developed in New Zealand where Pasifika heritage and other community languages can flourish. New Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In the context of ethnic identity and language, Anae (1998) found that Samoa-born Samoans and elders viewed the Samoan language as a marker of Samoan identity and that those not able to speak it were considered fiapālagi (reflecting Pākehā ways). Recent research by Anae and Peterson (2020) and Samu et al (2019) found that not being able to speak their own community language was an ethnic identity stress point for some Pasifika participants. These findings highlight the potential identity challenges that monolingual and bilingual Pasifika peoples likely face in Aotearoa New Zealand.…”
Section: Ethnic Identity Wellbeing and Languagementioning
confidence: 98%
“…In the context of ethnic identity and language, Anae (1998) found that Samoa-born Samoans and elders viewed the Samoan language as a marker of Samoan identity and that those not able to speak it were considered fiapālagi (reflecting Pākehā ways). Recent research by Anae and Peterson (2020) and Samu et al (2019) found that not being able to speak their own community language was an ethnic identity stress point for some Pasifika participants. These findings highlight the potential identity challenges that monolingual and bilingual Pasifika peoples likely face in Aotearoa New Zealand.…”
Section: Ethnic Identity Wellbeing and Languagementioning
confidence: 98%
“…Physiotherapists should seek guidance to understand these elements in the communities they are working with to improve their contextual cultural awareness, their cultural sensitivity, and ultimately their cultural safety (Martin, 2014). Language has been identified as a critical part of Pacific people's identity and sense of belonging in the world and a crucial marker for their long-term wellbeing (Samu et al, 2019). Physiotherapists should promote native language in their interactions with Pasifika communities.…”
Section: Physiotherapy Recommendations and Implications For Practicementioning
confidence: 99%
“…In this study, the inclusion of elders was highly valued by the participants and was seen to strengthen social cohesion. Interactions with elders provided a platform for sharing oral heritage via storytelling, which may be of particular importance as exposure to language at an early age is critical (Samu et al, 2019). Benefits may also prevail for both the younger and older generations through influences on mental, spiritual, cultural, and family areas of the Fonofale model of health and wellbeing.…”
Section: Physiotherapy Recommendations and Implications For Practicementioning
confidence: 99%
“…The steady decline of heritage language use, the lack of intergenerational language transmission and the shift to English among Pacific Islanders in Australia and New Zealand has long been apparent (McCaffery & McFall-McCaffery, 2010). The low self-esteem and identity insecurity that often follows the loss of heritage languages has also been well documented (Samu, et al, 2019). Therefore, our discussion of the literature that informed our study focuses on the value of bilingual language programmes for children's early years development.…”
Section: Introductionmentioning
confidence: 99%